A School-Based RISE Intervention to Improve Adolescent Reproductive Health Knowledge, Attitudes and Self- Reported Skills: A Quasi-Experimental Study - Nani Winani; Irna Nursanti; Dhea Natashia; Rohman Azzam (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2026)
ObjectiveThis study examined the effectiveness of the Reproductive Information for Healthy Empowerment (RISE) intervention in promoting improvements in reproductive health knowledge, attitudes, and self-reported skills among female adolescents.MethodsA quasi-experimental pre-test–post-test control group study was conducted among 130 female students aged 15–19 years from a vocational health school in Indonesia. Participants were recruited using convenience sampling and allocated at the class level to an intervention group (n = 65) and a control group (n = 65). The RISE intervention was delivered over four weeks through structured modules combining video-based learning and interactive discussions. Data collection was conducted using a structured questionnaire assessing reproductive health knowledge, attitudes, and self-reported skills. Statistical analyses included paired and independent t-tests, followed by multivariable linear regression to adjust for potential confounders.ResultsThe intervention group demonstrated significantly greater improvements in reproductive health knowledge (mean difference = 1.91, p < 0.001), attitudes (mean difference = 3.63, p < 0.001), and self-reported skills (mean difference = 1.15, p = 0.003) compared with the control group. Multivariable analysis confirmed that the RISE intervention remained significantly associated with improvements in all outcomes after adjustment for confounding variables.ConclusionThe RISE intervention effectively improved adolescents’ reproductive health knowledge, attitudes, and self-reported skills, supporting its integration into school-based reproductive health promotion programs.